Decision Making Model for Temple Revitalization in Bali Using Fuzzy-SMARTER Combination Method - Erlina Putri, Ni Putu Mita; Sudipa, I Gede Iwan; Wiguna, I Komang Arya Ganda; Sarasvananda, Ida Bagus Gede; Sunarya, I Wayan (Politeknik Ganesha Medan, 2024)
Bali is dominated by Hindus and temples as places of worship. Revitalization is carried out periodically in order to preserve the temple. Many factors are taken into consideration in revitalization decisions so that they can be approved by a group or government. Through the decision-making model of temple revitalization in Bali, the entire complexity of decision-making factors can be integrated so as to produce an objective priority ranking of improvements as supporting data for a revitalization decision. The combination of fuzzy sets and the SMARTER (Simple Multi Attribute Rating Technique Exploiting Rank) method can help solve unstructured problems in determining temple revitalization decisions. The calculation between the Alternative sacred building and the complexity factor criteria with a final value of more than 0.5 is included as a revitalization priority suggestion.